2006
DOI: 10.1104/pp.106.077982
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Arabidopsis Seeds Is Dependent on Glutathione Biosynthesis within the Embryo  

Abstract: Glutathione (GSH) has been implicated in maintaining the cell cycle within plant meristems and protecting proteins during seed dehydration. To assess the role of GSH during development of Arabidopsis (Arabidopsis thaliana [L.] Heynh.) embryos, we characterized T-DNA insertion mutants of GSH1, encoding the first enzyme of GSH biosynthesis, g-glutamyl-cysteine synthetase. These gsh1 mutants confer a recessive embryo-lethal phenotype, in contrast to the previously described GSH1 mutant, root meristemless 1(rml1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
212
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(221 citation statements)
references
References 63 publications
7
212
1
1
Order By: Relevance
“…Even ntra ntrb rml1 homozygous seeds are able to sustain some growth on a glutathione medium, showing that their viability is not impaired. This notion was recently contradicted by the characterization of a knockout mutant in the GSH1 gene in which no seed formation takes place (Cairns et al, 2006). This mutant revealed that a small amount of GSH is necessary for embryo development.…”
Section: The Overlapping Role Of Ntr and Glutathione In Meristematic mentioning
confidence: 86%
“…Even ntra ntrb rml1 homozygous seeds are able to sustain some growth on a glutathione medium, showing that their viability is not impaired. This notion was recently contradicted by the characterization of a knockout mutant in the GSH1 gene in which no seed formation takes place (Cairns et al, 2006). This mutant revealed that a small amount of GSH is necessary for embryo development.…”
Section: The Overlapping Role Of Ntr and Glutathione In Meristematic mentioning
confidence: 86%
“…Antisense lines for Arabidopsis GSH1 indicated that 5% of wild-type GSH, which would result in an E GSH of ϷϪ240 mV, already limits the growth rate and renders plants more sensitive to environmental stress (40). Progressive growth inhibition and increasing stress sensitivity is also apparent for the even more severely affected rml1 mutant, which has Ͻ5% of wild-type GSH, and embryo lethal gsh1 deletion mutants (41,42). Deletion of GR and a concomitant 21-fold increase in GSSG have been reported to cause oxidation of GRXs in S. cerevisiae (20).…”
Section: Gr1 Is Not Essential For Plant Developmentmentioning
confidence: 99%
“…Although MCB preferentially labels GSH, the interpretation of images is complicated by vacuolar sequestration of GSH-bimane conjugates (22,23). In addition, leaf cells can be difficult to load with the dye because of limited permeability of the leaf cuticle and the need for vacuum infiltration of leaf fragments.…”
Section: Identification Of Mutants Resistant To a Gsh Biosynthesis Inmentioning
confidence: 99%